Compression screws and buttress plate versus compression screws only for Hoffa fracture in Chinese patients: a comparative study. Issue 1 (January 2019) - Lu*, Bangbao; Zhao*, Shushan; Luo, Zhongwei; Lin, Zhangyuan; Zhu, Yong
Objective: To compare compression screws and buttress plate (CS plus BP) with compression screws only (CS) in treating patients with Hoffa fracture. Methods: This retrospective study included Chinese patients with Hoffa fracture treated by open reduction and internal fixation. Radiographs and clinical outcomes (range of movement [ROM], bone union and Knee Society Score [KSS]) were compared between patients treated using CS plus BP versus CS only. Results: At 4 months following surgery, significantly better outcomes were shown in the CS plus BP group ( n  = 24) versus CS only group ( n  = 21) regarding ROM (120.4 ± 5.2° versus 110 ± 7.1°) and KSS (85.5 ± 4.1 versus 79.7 ± 3.3). At the 12-month follow-up, significantly better outcomes were maintained in the CS plus BP versus CS only group regarding ROM (126.2 ± 7.4° versus 120.5 ± 8.2°) and KSS (88.3 ± 4.6 versus 84.2 ± 4.0). At the final follow-up, all patients had normal fracture healing and no malunion, nonunion or reduction loss. Conclusions: Fixation with CS plus BP for Hoffa fracture is effective and reliable, and may provide more adequate stability and better outcomes versus CS only.